The revised fundamentals of caregiving : a novel - Evison, Jonathan (Algonquin Books of Chapel Hill, 2012)
After losing virtually everything meaningful in his life, Benjamin trains to be a caregiver, but his first client, a fiercely independent teen with muscular dystrophy, gives him more than he bargained for and soon the two embark on a road trip to visit the boy's ailing father.